Emergence of novel ST1299 vanA lineages as possible cause for the striking rise of vancomycin resistance among invasive strains of Enterococcus faecium at a German university hospital - Giuseppe Valenza; David Eisenberger; Sven Voigtländer; Rayya Alsalameh; Roman Gerlach; Sonja Koch; Bernd Kunz; Jürgen Held; Christian Bogdan (Microbiology Spectrum, 2023)
ABSTRACT Since 2019, we have observed a remarkable rise of vancomycin resistance among invasive strains of Enterococcus (E.) faecium at the University Hospital Erlangen (UKER), a tertiary-care hospital in Germany. Here, we analyzed the genetic diversity of E. faecium isolated from blood cultures of in-patients by core genome multilocus sequence typing to see whether the occurrence of vancomycin resistance was associated with the spread of new clonal lineages. Between January and December 2022, 37 consecutive non-duplicate isolates were included in this study. Resistance to vancomycin was detected in 15 isolates (40.5%). The affected patients had a median age of 65 years, and 26 of them (70.3%) were males. Patients with bloodstream infection caused by vancomycin-resistant E. faecium (VREfm) or vancomycin-susceptible E. faecium (VSEfm) showed a similar in-hospital mortality rate (33.3% vs 27.3%, P = 0.692), indicating that VREfm were not more virulent than VSEfm. In contrast, the genetic diversity was higher in VSEfm (15 clonal lineages) than in VREfm isolates (seven clonal lineages). The majority of VREfm isolates (73.2%) belonged to only three clonal lineages: ST117/CT71 vanB (n = 4), which is the most commonly detected vancomycin-resistant lineage in Germany, and two novel ST1299 vanA lineages classified as CT3109 (n = 4) and CT1903 (n = 3). We conclude that the high rate of vancomycin resistance among invasive E. faecium isolates at UKER could be associated with the emergence of novel ST1299 vanA lineages, which is likely to be relevant also for other hospitals and countries. Future studies will focus on the prevalence of ST1299 vanA in the general population. IMPORTANCE The proportion of VREfm among all Enterococcus faecium isolated from blood cultures in German hospitals has increased in the period 2015–2020 from 11.9% to 22.3% with a country-wide spread of the clonal lineage ST117/CT71 vanB. In this study, we provided useful information about the genetic diversity of invasive strains of E. faecium. Moreover, our findings confirm the nosocomial spread of novel ST1299 vanA lineages, which recently had a rapid expansion in Austria and the south-eastern part of Germany.